2018
DOI: 10.1111/bjh.15582
|View full text |Cite
|
Sign up to set email alerts
|

Study of gene polymorphisms as predictors of treatment efficacy and toxicity in patients with indolent non‐hodgkin lymphomas and mantle cell lymphoma receiving bendamustine and rituximab

Abstract: Bendamustine is used in combination with rituximab (BR) to treat indolent non-Hodgkin lymphomas (iNHL) and mantle cell lymphoma (MCL). The variability in treatment efficacy and toxicity could be related to single nucleotide polymorphisms (SNPs) in immune response genes. We would like to show a correlation between SNPs and treatment outcome in iNHL and MCL patients receiving BR. We investigated some SNPs that had already been associated with NHL outcome. Samples were genotyped for the IL2 (rs2069762), IL10 (rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…According to this, PFS is a good alternative endpoint. Some studies for indolent lymphoma also use PFS as the endpoint 39–41 . Our new nomogram efficiently discriminated patients in the low‐risk group and high‐risk group based on PFS and proved to be valuable with respect to stratifying OS.…”
Section: Discussionmentioning
confidence: 98%
“…According to this, PFS is a good alternative endpoint. Some studies for indolent lymphoma also use PFS as the endpoint 39–41 . Our new nomogram efficiently discriminated patients in the low‐risk group and high‐risk group based on PFS and proved to be valuable with respect to stratifying OS.…”
Section: Discussionmentioning
confidence: 98%
“…Variants with a low frequency of SOX11 negativity and IGHV-mutated genes are more indolent and associated with better prognosis. It is useful to confirm SOX11 negativity with hypermutated IGHV to identify a clearly indolent disease [ 54 , 55 ]. Sílvia et al demonstrated that SOX11 knockdown reduced engrafted tumor growth in vivo, which is consistent with the indolent clinical course of human SOX11-negative MCL [ 38 ].…”
Section: The Expression Level Of Sox11mentioning
confidence: 99%
“…In addition, a broad range of nanomaterials have been used for the translation to NMs, which include nanosuspensions, polymeric nanoparticles (NPs), iron oxide NPs, metallic NPs, , nanopores, dendrimers, liposomes, etc. Therefore, NMs have improved and extended the pharmacokinetic, solubility and stability properties of a series of drug molecules that have been widely used in various biomedical applications, including particular drug delivery, therapy, imaging, and diagnostics. , However, the use of NMs continues to be characterized by numerous unclear effects on human health and various biological barriers to be overcome, which include stability, surface modification and functionalization, multimode functions, efficient drug delivery, a balance between the efficacy and side effects, etc. , …”
Section: Introductionmentioning
confidence: 99%
“…1,35 However, the use of NMs continues to be characterized by numerous unclear effects on human health and various biological barriers to be overcome, which include stability, surface modification and functionalization, multimode functions, efficient drug delivery, a balance between the efficacy and side effects, etc. 1,36 Nanohybrids (NHs) consisting of noble metal and magnetic components are promising for applications in a broad range of areas including energy conversion, 37,38 medical imaging, 39,40 and disease detection, 41−43 owing to their unique physicochemical properties, high stability, and multimode properties (i.e., magnetic and electromagnetic sensitivity). 44 Moreover, proper modification of the surface of these NPs and/or conjugation with certain medicines or organic components leads to a wide therapeutic window and clinical application with no or markedly reduced side effects on healthy cells and/ or tissues.…”
Section: ■ Introductionmentioning
confidence: 99%